ANALISIS PENGARUH ROA DAN CR TERHADAP PBV DENGAN DPR SEBAGAI VAIABEL INTERVENING - Ningfira Gitaningtyas; Umrotul Khasanah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Company value is a form of company achievement seen from the point of view of several parties such as investors who attribute the value of a company to its share price. There are several factors that can influence the firm value, including profitability, liquidity and dividend policy. In this study using a quantitative approach. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020 by using